The sustainability of zakat distribution from MAIK towards less fortunate people (ASNAF group) / Nor Radhiah Mohd Riduan - Mohd Riduan, Nor Radhiah (2008)
This study investigates the sustainability of zakat distribution from Majlis Agama Islam Dan Adat Istiadat Melayu Kelantan (MAIK) towards less fortunate people. The objective of this study are to determine that the assistance can help receivers in alleviate poverty, to identify whether the zakat assists from MAIK can increase income support of zakat receivers, to determine that zakat distribution to less fortunate people can reduce income inequality and the last is to measure that the zakat distribution will help the receivers in emergency relief. This study use a standard methodology which is the population in this research is among the less fortunate people (Asnaf group) who are eligible to receive a zakat assists from MAIK. The study uses a sample of 60 respondents among the receivers of zakat money from MAIK and gets the data collection from primary and secondary data. From the primary data, the study used questionnaire while based on the secondary data, the study used newspaper articles, journal from internet and books at the library. For the finding, the study used Statistical Procedure of Social System (SPSS). The result show the positive relationship between the dependent variable which is the sustainability of zakat distribution and independent variables which are alleviates poverty; reduce income inequality, income support and emergency relief. The finding of the study is proven from reliability test, cross tabulation analysis, chi-square and correlation for every questionnaire. Therefore, the finding was rejected the all null hypothesis for every questionnaire of all independent variables.